Ultra-long period cepheids: observations, theory, and use as standard candles - Ilaria Musella (Frontiers in Astronomy and Space Sciences)
This paper presents a review of the main properties of ultra-long-period Cepheids (ULPs). The analysis is based on the largest sample of known ULPs, comprising 73 pulsators, including the first ULP discovered in the Milky Way. These intrinsically highly luminous variables can be observed at distances greater than 100 Mpc. They have been hypothesized as the extension of classical Cepheids at higher periods, masses, and luminosities. However, whether this is the case or they constitute a distinct class of pulsators remains to be verified, as well as their suitability as standard candles. If confirmed as reliable distance indicators, they would enable direct measurements of cosmological distances without relying on secondary distance indicators, reducing potential systematic errors in the calibration of the cosmic distance scale. In addition, the potential of the upcoming Rubin LSST survey to enhance the sample with high-quality data is investigated.